Chinese medicine Di-Huang-Yi-Zhi protects PC12 cells from H2O2-induced apoptosis by regulating ROS-ASK1-JNK/p38 MAPK signaling - Li-Min Zhang; Rong-Rong Zhen; Chao Gu; Tian-Li Zhang; Yue Li; Miao Jin; Bing Hu; Hong-Mei An (BMC, 2020)
Abstract Background Oxidative stress mediates the nerve injury during the pathogenesis of Alzheimer's disease (AD). Protecting against oxidative stress damage is an important strategy to prevent and treat AD. Di-Huang-Yi-Zhi (DHYZ) is a Chinese medicine used for the treatment of AD, but its mechanism remains unknown. This study is aimed to investigate the effect of DHYZ on H2O2 induced oxidative damage in PC12 cells. Methods PC12 cells were treated with H2O2 and DHYZ. Cell proliferation was detected by Cell counting kit-8 (CCK-8) assay. Cytotoxicity of H2O2 was measured by lactate dehydrogenase (LDH) release assay. Apoptosis were identified by Annexin V-FITC/PI staining. Caspase 3 activity was detected by commercial kit. Mitochondrial membrane potential (MMP) was detected by JC-1 staining. Reactive oxygen species (ROS) was 2', 7'-Dichlorodihydrofluorescein diacetate (DCFH-DA) staining. Protein expression and phosphorylation was identified by western blot. Results The results showed that DHYZ antagonized H2O2-mediated cytotoxicity and proliferation inhibition. DHYZ reduced ROS production, stabilize mitochondrial membrane potential, inhibit Caspase-3 activity and apoptosis induced by H2O2. In addition, DHYZ inhibited the phosphorylation of ASK1, JNK1/2/3 and p38 MAPK which were up-regulated by H2O2. Conclusions The present study suggested that DHYZ protected PC12 cells from H2O2-induced oxidative stress damage and was related to inhibition of ROS production and ASK1-JNK/p38 MAPK signaling. The present study provides experimental evidence for the application of DHYZ for the management of oxidative stress damage and AD.